2016
DOI: 10.1108/lm-03-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Training needs of paraprofessional library staff in university libraries in South-East Nigeria

Abstract: Purpose The purpose of this paper is to investigate the training needs of paraprofessional library staff in university libraries in South-East Nigeria with the objective to find out their training needs, the training programmes available to them, their utilization of training opportunities, hindrances to their training and strategies for enhancing training for them. Design/methodology/approach The descriptive survey design and total enumeration technique were used for the study. The instrument for data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Lack of adequate skills on the part of library staff to fully use the IS coupled with inadequate management and system support was clearly indicated. Similar findings were recorded by older studies by Ibegbulam and Eze (2016), Makori (2013), Mapulanga (2013), Adeleke and Olorunsola (2010), Adeyoyin (2005), Asogwa (2014) as well as Mutula (2004).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lack of adequate skills on the part of library staff to fully use the IS coupled with inadequate management and system support was clearly indicated. Similar findings were recorded by older studies by Ibegbulam and Eze (2016), Makori (2013), Mapulanga (2013), Adeleke and Olorunsola (2010), Adeyoyin (2005), Asogwa (2014) as well as Mutula (2004).…”
Section: Introductionsupporting
confidence: 91%
“…Adeleke and Olorunsola (2010) conducted a study on the use of online tools for cataloguing and classification in Nigerian university libraries and found that lack of skills on the part of library staff in using the tools is a major challenge. Their findings on ICT skills were also echoed by Adeyoyin (2005) as well as Ibegbulam and Eze (2016) by stating that the rate of ICT literacy among Nigerian library staff is very low. Libraries also encounter subscription challenges dealing with licencing agreement coupled with lack of experience of completing online forms, difficulty with the use of credit cards coupled with the risk of internet fraud.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The target population for the study was 93 professional university library personnel from the 13 participating libraries. The term "professional librarian" refers to library staff holding at least a first degree in Library and Information Science (Ibegbulam and Eze, 2016) and occupying professional levels one-three of the Zimbabwe National Qualifications Framework, namely, the positions of university library director, deputy director, sub-librarian, assistant librarian and systems librarian (Ministry of Higher and Tertiary Education, Science and Technology Development, 2018). The target population of the study was 93 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, developments in Information Technology also necessitate participation in CPD activities (Imam et al , 2021; Issa, 2021). Moreover, advances in organizational methods and job-related tasks, a desire to exchange ideas and enhance one’s or the library’s reputation, and personal curiosity are other motivating factors that repeatedly occur in previous works (Clapton, 2010; Ibegbulam and Eze, 2016). Similarly, other studies have explored challenges related to LIS CPD.…”
Section: Literature Reviewmentioning
confidence: 99%